Characterization of 3D-Printed Human Regulatory T-Cells. (July 2018) - Kim, Juewan; Yue, Zhilian; Liu, Xiao; Hope, Christopher; Rojas-Canales, Darling; Drogemuller, Christopher; Carroll, Robert; Barry, Simon C; Wallace, Gordon G; Toby Coates, P.
Abstract : Introduction: 3D bioprinting is an innovative technology that allows for the rapid and precise fabrication of complex 3D architectures. Co-printing of regulatory T-cells (Tregs) and islets in a 3D-printed lattice may overcome current immunosuppressive obstacles in islet transplantation. This project aims to evaluate the effect of bioprinting on Treg viability and functionality and to evaluate what effect modifying the hydrogel 'ink' with IL-2 may have on these parameters. Methods: CD4 + CD25 hi CD127 low natural Tregs (nTregs) and CD4 + CD45RA + (naïve) T cells were isolated from human blood by FACS. Naïve CD4 + T-cells were induced to a Treg phenotype (iTreg) by culture with TGF-β, all-trans retinoic acid (ATRA) and rapamycin. nTregs and iTregs were expanded with IL-2 and anti-CD3/28-conjugated beads over 14 days. These cells were either suspended in media ('non-printed'), or printed to a 6mm diameter disc structure (at 2x106 cells/mL) within an alginate-gelMA hydrogel, photo-crosslinked (at 400nm) and chemically crosslinked with CaCl2 (2% w/v). These 'printed' cells were recovered by dissolving the hydrogel with TrypLE Express. Viability and Treg functional markers were quantified by flow-cytometry using propidium iodide and anti-LAP, CD69, CD39 and CTLA-4 antibodies. Results and Discussion: The viability of nTregs decreased from 92% (±1.6%) to 85% (±2.3%) with IL-2, and from 89% (±1.9%) to 80% (±4.6%) without IL-2, upon printing (p<0.0001 for both). iTreg viability decreased from 91% (±2.2%) to 87% (±3.4%) with IL-2, and from 91% (±2.4%) to 85% (±1.5%) without IL-2, upon printing (p=0.0042 and <0.0001, respectively). This demonstrated that the effect of bioprinting, on both nTreg and iTreg viability, is statistically significant but minimal. Hydrogel modification with IL-2 had no significant effect on viability at day 1. However, at day 3, IL-2 significantly increased printed nTreg viability by 15% (72±4.8%) compared without IL-2 (57±8.9%, p=0.0003). While this demonstrated the merit of hydrogel modification with IL-2, it did not mimic the 48% improvement shown under non-printed conditions (91±2.4% with IL-2 and 53±9.3% without IL-2, p<0.0001). This may be due to IL-2 leaching into the media, decreasing the concentration in the hydrogel. IL-2 retention within the hydrogel could be improved using a microsphere sustained-release system. Moreover, no decrease in LAP, CD69, CD39 or CTLA-4 expression was observed upon printing, suggesting functional markers are not diminished by the printing process. Conclusion: Firstly, our data suggests nTregs and iTregs can be safely bioprinted with minimal effect on viability or functional marker expression. Secondly, we demonstrate that hydrogel modification with IL-2 has a positive impact on the survival of bio-printed nTregs. Finally, this study serves as proof of principle for the capacity of immune cells to survive within hydrogel structures. Figure. No caption available.